Musical and cognitive abilities in older adults with mild cognitive impairment. (January 2021) - Petrovsky, Darina V; Johnson, Julene K; Tkacs, Nancy; Mechanic-Hamilton, Dawn; Hamilton, Roy H; Cacchione, Pamela Z
The objective of this cross-sectional study was to determine the extent and nature of self-reported musical abilities in persons with mild cognitive impairment (MCI). We recruited 60 older adults with a diagnosis of MCI from the Alzheimer's disease Core Center. We evaluated self-reported musical abilities using the Goldsmiths General Musical Sophistication Index. We examined correlations between musical abilities and neuropsychological measures of verbal learning and memory, processing speed, executive function, verbal fluency, naming, and visuoconstructive abilities, while controlling for key demographic and participant characteristics. Older adults with MCI reported varying degrees of musical abilities. Nearly half of participants reported that they did not engage in regular, daily practice of a musical instrument. When adjusting for key demographic and participant characteristics, we found modest associations between four musical ability subfactors (active engagement, perceptual abilities, musical training, and emotional engagement with music) with three cognitive abilities: verbal fluency, executive function, and verbal naming. Except for the emotional engagement with music subfactor, none of the remaining musical ability subfactors correlated with any demographic or participant characteristics. While our study findings provided support for the relationship between musical and cognitive abilities in older adults with MCI, this relationship warrants further investigation.